Gene transcription patterns in response to low level petroleum contaminants in Mytilus trossulus from field sites and harbors in southcentral Alaska. (January 2018) - Bowen, Lizabeth; Miles, A. Keith; Ballachey, Brenda; Waters, Shannon; Bodkin, James; Lindeberg, Mandy; Esler, Daniel
Abstract: The 1989 Exxon Valdez oil spill damaged a wide range of natural resources, including intertidal communities, and post-spill studies demonstrated acute and chronic exposure and injury to an array of species. Standard toxicological methods to evaluate petroleum contaminants have assessed tissue burdens, with fewer assays providing indicators of health or physiology, particularly when contaminant levels are low and chronic. Marine mussels are a ubiquitous and crucial component of the nearshore environment, and new genomic technologies exist to quantify molecular responses of individual mussels to stimuli, including exposure to polycyclic aromatic hydrocarbons (PAHs). We used gene-based assays of exposure and physiological function to assess chronic oil contamination using the Pacific blue mussel, Mytilus trossulus . We developed a diagnostic gene transcription panel to investigate exposure to PAHs and other contaminants and its effects on mussel physiology and health. During 2012–2015, we analyzed mussels from five field sites in western Prince William Sound, Alaska, with varying oil histories from the 1989 Exxon Valdez oil spill, and from three boat harbors in the area. Gene transcription patterns of mussels from harbors were consistent with elevated exposure to PAHs or other contaminants, whereas transcription patterns of mussels sampled from shorelines in areas affected by the oil spill indicated no PAH exposure.